Prevention of Nosebleeds and Modern Clinical Diagnostic Methods - Dilmurod o'g'l, Avazov Umrzoq; M. T, Prof. Nasretdinova (Journal of Science in Medicine and Life, 2025)
These methods of treatment require anesthesiological and resuscitation support (local, regional and general anesthesia can be performed). In case of severe blood loss, transfusions of colloid and crystalloid preparations, as well as transfusions of blood components, are performed. Epistaxis is the most common form of external bleeding, accompanied by a runny nose, often associated with facial trauma, and occurs in both adults and children. The most common damage to blood vessels occurs in the area of the nasal septum. The development of bleeding from the structures in the bridge of the nose often occurs in patients with atherosclerosis, blood diseases, or during surgical interventions on the nose for therapeutic or aesthetic purposes.